Personality Correlates of Disciplinary Infractions in a Military-Style Residential Program for Adolescents. Issue 1 (2nd January 2021) - Charles, Nora E.; Floyd, Paula N.; Cole, Madison L.; Barry, Christopher T.
ABSTRACT: This study examines personality correlates of disciplinary infractions in a sample of adolescents in a military-style residential program, an understudied but at-risk sample. Ninety-nine boys ( Mage  = 16.9 years) self-reported traits associated with externalizing psychopathology and problem behaviors. Additionally, each participant's disciplinary record was obtained from the program. Disciplinary infractions were classified into five categories: physical aggression, verbal aggression toward peers, conflicts with staff, disruptive behavior, and rule-breaking. Principal component analysis indicated four distinct elements that underlie results on the self-report measures: (1) aggressive tendencies, (2) impulsivity and instability, (3) sensation seeking, and (4) narcissism. Subsequent regression analyses revealed differential associations between these components and counts of infractions across categories. These findings can inform research on the personality-based correlates of institutional misconduct, and they may also help staff in residential settings better manage or prevent some of the disciplinary problems they experience.